The effectiveness of flipbook-based e-modules in increasing student creativity in nail art subject in higher education - Rahmiati Rahmiati; Mutia Putri; Engkizar Engkizar; Marzni Mohamed Mokhtar (Jurnal Pendidikan Vokasi, 2023)
Incorporating technology into the learning process has resulted in the development of various new media for lecturers to use in delivering subject matter. Furthermore, the material presented is intended to enable students to develop creative and innovative ideas in higher education vocational majors in makeup and beauty. The purpose of this study is to determine how effective the flipbook-based module is in increasing student creativity in nail art subject at the Department of Beauty and Cosmetology at Universitas Negeri Padang. This study employs a quantitative and experimental approach (Group Pretest-Posttest Design). Data were collected from thirty respondents using a Likert scale questionnaire and a pre-test and post-test of nail art practice skills. All respondents are students in the Department of Cosmetology and Beauty, Faculty of Tourism and Hospitality, for the 2021/2022 academic year. All data were then analyzed descriptively and correlated using SPSS 23 software. Overall, the analysis results showed that using flip book-based e-modules could increase students' creativity in nail art subjects. These results can be proven by the effectiveness test of students' creativity, with an average value of 71.9%. Furthermore, the correlation analysis revealed a significant value of 0.05 and a t-score of 7.083> t-table of 2.045. The results of this study imply that it can provide references for education in choosing learning media and strategies for delivering learning materials that are effective in increasing creativity. Furthermore, this can be used as a basis for further development to produce effective media and learning approaches.